Pengaruh Metode Bercerita terhadap Peningkatan Kemampuan Bahasa Ekspresif pada Anak Intelektual Disabilitas di Surakarta - Luluk Nasihah; Gunawan Gunawan; Sudarman Sudarman (Jurnal Terapi Wicara dan Bahasa, 2026)
Background: Children with intellectual disabilities generally experience difficulties in expressive language skills, which impact communication, social interaction, and the learning process. Learning methods appropriate to the child's cognitive characteristics are needed, one of which is storytelling, which is considered effective in stimulating vocabulary, sentence structure, and speaking confidence. Objectives: This study aims to determine the effect of storytelling on improving expressive language skills in children with intellectual disabilities in Surakarta. Methods: The study used a quantitative quasi-experimental design with a one-group pretest–posttest design. The sample consisted of 15 children with intellectual disabilities, selected using a total sampling technique. Data collection was conducted through observation and a validated Expressive Verbal Vocabulary Test (EVO). The storytelling intervention was administered over eight structured sessions. Results: The Wilcoxon Signed Rank Test analysis showed an increase in expressive language skills in the majority of respondents after the storytelling intervention. Fourteen of the 15 children experienced an increase in their post-test scores compared to their pre-test scores, and the statistical test results showed a significant difference (p < 0.05). Conclusion: The storytelling method is effective in improving expressive language skills in children with intellectual disabilities and can be used as an alternative intervention strategy in learning and speech therapy. Keywords: Storytelling Method, Expressive Language, Intellectual Disability.